GENDER APPROACH TO THE STUDY OF PROFESSIONAL IDENTITY AMONG STUDENTS - Rakhmonova, Guzal Jamshidovna (SCIENCE and SOCIETY, 2026)
The article analyzes students’ professional identity as both an indicator and a result of successful adaptation to academic and sociocultural environments. It highlights its role in reducing anxiety, insecurity, and internal tension. Special attention is given to gender differences in the formation of professional identity.